An Experimental and Statistical Analysis on Dry Sliding Wear Failure Behavior of Incoloy 825 at Elevated Temperatures - Cavdar, Faruk; Gunen, Ali; Kanca, Erdogan; Er, Yusuf; Gok, Mustafa Sabri; Campos-Silva, Ivan; Olivares-Luna, M. (Springer, 2023)
Incoloy 825 is a Ni-Fe-Co superalloy which is used at temperatures in a wide range of temperatures from room temperatures to 650 degrees C. To overcome difficulty of testing of wear properties of the material in this wide range, Response Surface Methodology is used to assess the wear behaviors such as coefficient of friction (CoF), wear track area and specific wear rate under varying dry sliding test variables such as sliding speed, load and especially temperature. Central composite design was performed to determine experimental sets of independent parameters. Dry sliding wear tests with these parameter sets were carried out on the Incoloy 825. The response surfaces constructed by using these test results revealed that the temperature, load, and speed affect response variables in a complex way. The CoF is negatively influenced by increase in load and speed, but the CoF behaves in adverse manner in high temperatures, as shown by the established response model. Wear track area tends to decrease as the temperature rises up to 650 degrees C. In high temperatures, the wear rate reduces as the load increases, but it rises when the sliding speed increases. SEM and EDS analyses showed that the wear behavior changed from plastic deformation to oxidation type wear mechanism with the increase in temperature, load and speed.
Keywords: failure mechanisms; friction; response surface methodology; superalloy; wear